Safety and employee health and well-being - Andrei, Daniela; Ochoa, Paola; Griffin, Mark (Routledge, 2018)
This book presents a collection of studies that address current and forthcoming organizational challenges and offer realistic solutions to support leaders and managers seeking to balance and value the contribution of people with long-term ...